Faktor–Faktor Yang Mempengaruhi Minat Wisatawan Berkunjung Ke Bukit Gundaling Berastagi Di Kabupaten Karo - Bakti Gunawan; Dameria Girsang (Tourism, Hospitality And Culture Insights Journal, 2022)
This reasecrch aims to identify what factors influences the interest of tourist who want to visit Bukit Gundaling Berastagi. This research used confirmatory aspect analysis information analysis methods. KMO aspect analysis, multiple regression analysis, t test, f test, and the coefficient of determination. 2 component aspects that influence the attention of tourist visiting Bukit Gundaling Berastagi, namely the beauty of the sight ( 3.081 ) ≻ ( 1.98) and ease of accessibility ( 3.524 )< t table ( 1.98 ) the calculate Fvalue based on table 4.14 is 8.876 and the f table value is 2.46. These values are compared to obtain f count ( 75.284 ) ˃ f table ( 3.08 ), so H0 is rejected. Based on these result, it can be concluded that there is a significant influence between the Beauty of sight, ease of accessibility on tourist interest in visiting Bukit Gundalin Berastagi. Hypothesis testing can also be done by looking at the probability value. The rule of hypothesis testing is if sig ≤ α then H0 IS rejected and if sig > α, then H0 is accepted. Based on table 4.12, the value of is 0.000. This value is compared with ( 0.05 ) so that sig ( 0.000 ) < ( 0.05 ), so H0 is rejected and H4 is accepted. Based on these results, it can be concluded that there is a significant influence between the beauty of sight, ease of accessibility on tourist interest in visiting Bukit Gundaling Berastagi. The coefficient of determination ( R2) is 0587. This means that the influence of the beauty of sight and the ease of accessibility on the interest of tourist visiting Bukit Gundaling Berastagi is 58.7% while the remaining 41.3% is explained by other factors outside of this study.